Profile and Financing Access Gaps of MSMEs in Indonesia: evidence from ADB Asia SME Monitor 2024 - Asmar Yunus; Adriansyah Adriansyah; Anisatun Humayrah Rais; Andi Nurrahma Gaffar (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a central role in Indonesia’s economy, yet access to finance remains a persistent constraint for their growth and resilience. This study aims to map the profile of MSMEs and identify gaps in access to financing in Indonesia using data from the Asian Development Bank Asia Small and Medium-Sized Enterprise Monitor 2024. The study employs a descriptive approach based on a multidimensional framework of depth, breadth, and risk to examine MSME financing conditions. The analysis focuses on MSME landscape indicators and banking financing data, including credit ratios, distribution structure, and non-performing loans. The findings indicate that although MSME credit has increased nominally in recent years, the depth of financing remains relatively stable when measured against GDP and total bank credit. Financing is still concentrated in specific sectors and predominantly allocated for working capital, while credit risk in the MSME segment remains higher than the aggregate banking portfolio. These results suggest that improvements in MSME financing require not only credit expansion but also policies that strengthen financial depth, broaden access, and enhance risk mitigation. The study provides policy-relevant insights to support more inclusive and sustainable MSME financing in Indonesia.